Philosophy of man: selected readings - Dy, Manuel B (Makati City, 2001)
As textbook in the course Philosophy of Man, it is comprehensive in scope and deep in insights. The readings are not not too difficult to understand, with the exception of Gabriel Marcel's Primary and Secondary Reflection: The Existential Fulcrum . Thus, this revised edition contains a paragraph by paragraph interpretation of this difficult text by Marcel.
Keywords: Man; Philosophy